Effects of infection control measures on acquisition of five antimicrobial drug-resistant microorganisms in a tetanus intensive care unit in Vietnam - Schultsz, C; Nga, T; Thao, L; Campbell, J; Vien, L; Hoa, N; Hoang, N; Farrar, J; Wit, F; Bootsma, M; Bonten, M; Loan, H; et al. (2013)
Purpose: To quantify the effects of barrier precautions and antibiotic mixing on prevalence and acquisition of five drug-resistant microorganisms within a single tetanus intensive care unit at a tertiary referral hospital in Ho Chi Minh City, Vietnam. Methods: All patients admitted within the study period were included. After a 1-year baseline period, barrier precautions were implemented and the single empirical treatment ceftazidime was changed to mixing (per consecutive patient) of three different regimens (ceftazidime, ciprofloxacin, piperacillin-tazobactam). Markov chain modeling and genotyping were used to determine the effects of interventions on prevalence levels and the relative importance of cross-transmission and antibiotic-associated selection. Results: A total of 190 patients were included in year 1 (2,708 patient days, 17,260 cultures) and 167 patients in year 2 (3,384 patient days, 20,580 cultures). In year 1, average daily prevalence rates for methicillin-resistant Staphylococcus aureus (MRSA), extended spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae (excluding Klebsiella pneumoniae), Pseudomonas aeruginosa, gentamicin-resistant K. pneumoniae, and amikacin-resistant Acinetobacter species were 34.0, 61.3, 53.4, 65.7 and 57.1 %. After intervention, ceftazidime usage decreased by 53 %; the use of piperacillin-tazobactam and ciprofloxacin increased 7.2-fold and 4.5-fold, respectively. Adherence to hand hygiene after patient contact was 54 %. These measures were associated with a reduction of MRSA prevalence by 69.8 % (to 10.3 %), mainly because of less cross-transmission (88 % reduction), and of ESBL-producing Enterobacteriaceae prevalence by 10.3 % (non-significantly). In contrast, prevalence levels of the other three pathogens remained unaffected. Conclusion: The combination of simple infection control measures and antibiotic mixing was highly effective in reducing the prevalence of MRSA, but not of Gram-negative microorganisms. © 2013 The Author(s).